Argumentación jurídica sobre la falta de creación de política pública para la aplicación de justicia indígena de los pueblos Awa en la provincia del Carchi - Rosero Martínez, Carlos Gilberto (2015)
The research was by legal argumentation object on the lack of creation of public policy for the application of indigenous justice of the Awa people in the province of Carchi, broke problem based on the analysis of the current situation of the town where by a study could discover the origin in the lack of public policies applicable to the extent of their rights. To do own methodological parameters of the social sciences which engage the legal relationships with those who are reduced in their rights as is the Awa village in the province of Carchi was used. From the diagnosis of each of the methods a proposal that involves the character of the spirit of the rules that protect these rights holders who are currently being absorbed by the ordinary system it self it is made.